Pengembangan Produksi Tanaman Mint Berbasis Ekonomi Rumah Tangga di Kelurahan Banyurip, Kota Pekalongan - MAdil Danial Faza; Muhammad Bahiyyul Bayan; Inda Rohmatul Aini; M Fakhrul Anam; Rendra Rizki Lutfiansyah; Tin Herawati (Lembaga Penelitian dan Pengabdian kepada Masyarakat, Institut Pertanian Bogor, 2021)
The potential development of mint plants in the industrial business has a very promising opportunity as a processed product for packaged tea by Kelompok Wanita Tani (KWT) Delima in Banyurip, Pekalongan City. Various obstacles were found in the management and processing of mint plant cultivation into mint tea processed products. The community service program aims to overcome these problems through the propagation of mint plant raw materials so that it can produce quality mint plants. In addition, the existence of better processing of mint leaves, namely into mint leaf tea in dry form, will increase the selling value of mint leaves with marketing strategies carried out online and offline. The implementation of the service work program is carried out in three main stages; pre-production, production and post-production. The mint tea products produced were introduced to KWT members simultaneously with the optimization of the management and processing of mint plants into derivative products which were intensively emphasized through interactive counseling, training on mint product processing and packaging. Other steps taken are developing the quantity and quality of mint plants, processing mint tea, and marketing. Thus, the production of processed mint tea can run in a sustainable manner so as to improve the economy of the local community. Keywords: Banyurip, KWT, mint, tea